Investigasi Sistem Pemasaran Produk Halal Olahan Edamame Mitratani 27 Kabupaten Jember - Ach Faqih; Fais Faizul Hannan; Bastomi Dani Umbara; Izzul Ashlah (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Marketing is very important in the world of business or entrepreneurship, whether large scale or small, medium or large scale. Marketing is an accomplice of leading companies. As the company's front line in achieving profits, of course, the people in this section must have reliable abilities, be active, and also not give up easily when facing business competition to win market share of the business they rely on. In this case, it is very important to implement marketing strategies at PT Mitratani Dua Tujuh in order to meet the needs and desires of customers on a national and international scale. This type of research uses field research. This research is based on the researcher's interest in Edamame Processed Products PT. Mitra Tani Dua Tujuh, especially in marketing strategies for halal products (PT. Mitra Tani Dua Tujuh) PT. Mitratani Dua Tujuh begins with the production process to the edamame marketing process which involves many parties. With collaboration between business partners, edamame has been successfully marketed to local and international markets. The network involved in the production process is all PT employees. Mitratani is involved in the process of providing raw materials, the edamame cultivation process, and the edamame processing process in the factory. The network involved in the marketing process is all parties or institutions involved in the marketing process of PT Mitratani products, such as Mitratani 27 Outlate distributors, IKBI (Wives' Extended Family Association) Mitra Tani 27 employees, PT Perkebunan Nusantara, PT Rolas Medika Nusantara, UPTPS Tresna Werdha Jember, the Agro-Industry Workers Union (SPA) and several agencies that collaborate with Mitra Tani 27 Jember.